Ecological-Social-Economic Tourism Model as a Sustainability Strategy for Pokdarwis Pantai Gudang Garam - Sulian Ekomila; Masatoshi Ito; Abdullah Akhyar Nasution; Ratih Baiduri; Daniel Harapan Parlindungan Simanjuntak; Ismail Jahidin (Komunitas, 2026)
Through an ecological-social-economic tourism paradigm, this article explores the development of the Gudang Garam Beach tourist destination in Serdang Bedagai Regency by the Tourism Awareness Group (Pokdarwis).  This study analyzes the social aspects of empowerment, management strategies for optimization, and the aspects that enhance Pokdarwis evolution using a descriptive qualitative approach in combination with trend data on tourist visits.  The findings indicate that Pokdarwis not only played a role in the development of infrastructure and the improvement of local economic conditions, but also in the strengthening of social capital, multigenerational collaboration, and community resilience during the COVID-19 crisis.  The novel aspect of this study is the integration of three sustainability pillars—economic, social, and ecological—into a single operational paradigm for community-based tourism.  By illustrating how grassroots leadership and social participation motivate adaptive capacity in post-crisis contexts, this strategy expands theoretical discussions regarding sustainable tourism.  Therefore, the ecological-social-economic tourism model offers both practical guidelines and academic insight to develop community-based tourism management in Indonesia and comparable environments.